Neglecting the neglected: the objective evidence of underfunding in rheumatic heart disease. (30th March 2019) - Macleod, Colin K; Bright, Philip; Steer, Andrew C; Kim, Jerome; Mabey, David; Parks, Tom
Abstract: Background: Despite the substantial global burden of disease, rheumatic heart disease research receives little funding globally. Methods: Using data from the Global Burden of Disease Study and funding from the G-FINDER database, we propose a novel logarithmic disability neglect index (DNI) to describe disease burden using disability-adjusted life years relative to funding for 16 major tropical diseases. Results: Across a range of diseases, rheumatic heart disease received the least funding relative to disease burden (DNI=3.83). Other diseases facing similar underfunding include cysticercosis (DNI=2.71) and soil-transmitted helminths (DNI=2.41). Conclusions: Rheumatic heart disease remains severely underfunded relative to disease burden.